Aktualisasi Nilai Karakter Religius Berdasarkan Konsep Iman Menurut Imam Al Ghazali Di Sekolah Dasar - Achmad Akbar (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Elementary school as a forum for basic education is able to become a bridge to provide an understanding of religious values ​​from an early age to students so that they are not easily shaken by the development of the times that are able to leave religious character values. This writing aims to describe how the actualization of religious character values ​​based on the concept of faith according to Imam Al Ghazali at SD IT Al Ghazali Palangka Raya. This paper was prepared using a qualitative approach with the type of field research (field research) and descriptive qualitative research methods. Collecting data in this paper, using observation, interviews and documentation. Data analysis used the Miles and Humberman technique: the data analysis includes data collection, data reduction, data display, and conclusion drawing/veryfication. The results of the discussion are; 1) Faith according to Imam Al Ghazali is simply saying with the tongue, admitting the truth with the heart and practicing it with the limbs. 2) Actualization of Religious Character Values ​​at SD IT Al Ghazali Palangka Raya, is divided into two types, namely; a) Objective actualization through collaborative school institutional structures, b) Subjective actualization is the implementation of charity (deeds) of the religious character values ​​by students both inside and outside the school. 3) Actualization of Religious Character Values ​​based on the concept of faith according to Imam Al Ghazali; a) through integrated learning of Islamic religious education, students are able to pronounce answers as a result of translators from the heart who believe in the oneness of Allah and the blessings of Islam in learning. Keywords: Religious Values; Concept of Faith; Imam Al Ghazali; Elementary School.